A Cytokine Network Balance Influences the Fate of Leishmania (Viannia) braziliensis Infection in a Cutaneous Leishmaniasis Hamster Model - Paiva, Milla B.; Ribeiro-Romão, Raquel Peralva; Resende-Vieira, Larissa; Braga-Gomes, Thais; Oliveira, Marcia P.; Saavedra, Andrea F.; Silva-Couto, Luzinei; Albuquerque, Hermano G.; Moreira, Otacilio C.; Pinto, Eduardo Fonseca; Da-Cruz, Alda Maria; Gomes-Silva, Adriano (Frontiers in Immunology, 2021)
The golden hamster is a suitable model for studying cutaneous leishmaniasis (CL) due to Leishmania (Viannia) braziliensis. Immunopathological mechanisms are well stablished in the L. (L.) major-mouse model, in which IL-4 instructs a Th2 response towards progressive infection. In the present study, we evaluated the natural history of L. braziliensis infection from its first stages up to lesion establishment, with the aim of identifying immunological parameters associated with the disease outcome and parasitism fate. To this end, hamsters infected with 104, 105, or 106 promastigotes were monitored during the first hours (4h, 24h), early (15, 30 days) and late (50 days) post-infection (pi) phases. Cytokines, iNOS and arginase gene expression were quantified in the established lesions by RT-PCR. Compared to the 105 or 106 groups, 104 animals presented lower lesions sizes, less tissue damage, and lower IgG levels. Basal gene expression in normal skin was high for TGF-β, and intermediary for TNF, IL-6, and IL-4. At 4hpi, no cytokine induction was observed in the 104 group, while an upregulation of IL-6, IL-10, and IL-4 was observed in the 106 group. At 15dpi, lesion appearance was accompanied by an increased expression of all assessed cytokines, markedly in the 105 and 106 groups. Upregulation of all investigated cytokines was observed in the late phase, although less expressive in the 104 group. IFN- was the depending variable influencing tissue damage, while IL-6 was associated to parasite load. The network correlating gene expression and clinical and laboratorial parameters indicated inoculum-independent associations at 15 and 30dpi. A strong positive network correlation was observed in the 104 group, but not in the 105 or 106 groups. In conclusion, IL-4, IL-6, IL-10, and TGF-β are linked to L. braziliensis progression. However, a balanced cytokine network is the key for an immune response able to reduce the ongoing infection and reduce pathological damage.